The Antileukemia Activity of Natural Product HQ17(3) Is Possibly Associated with Downregulation of miR-17-92 Cluster. (22nd July 2014) - Liao, Ya-Chun; Lin, Tzu-Heng; Chen, Chih-Ying; Lin, Shwu-Bin; Au, Lo-Chun
Abstract : The compound 10′(Z), 13′(E), 15′(E)-heptadecatrienylhydroquinone [HQ17(3)] was purified from the sap of the lacquer tree Rhus succedanea . HQ17(3) has cytotoxic effect on cancer cells and can inhibit topoisomerase (topo) II α activity. We treated various cancer cells with different doses of HQ17(3) and found that leukemia cells were most sensitive to HQ17(3). After analysis of microRNA (miRNA) profiling, we found that treatment with HQ17(3) caused downregulation of miR-17-92 cluster in some leukemia cells. These changes partially restored the normal levels from leukemia-specific miRNA expression signature. Messenger RNAs of tumor suppressor proteins, such as pRB, PTEN, and Dicer, are targets of miR-17-92 cluster. Their protein levels were increased after the treatment. c-Myc is a regulatory protein for miR-17-92 gene. Similar to topo II α, we found that c-Myc decreased its activity after the HQ17(3) treatment, which may explain the downregulation of miR-17-92 cluster. Combined with 5-fluorouracil, NaAsO2, or ABT-737, HQ17(3) elicited additive inhibitory effects on leukemia cells. In conclusion, the high sensitivity of leukemia cells to HQ17(3) may be associated with the reduction of topo II α and c-Myc activities, as well as with the downregulation of the miR-17-92 cluster expression.